The Anishinaabeg of Chief's Point - Pucan, Bimadoshka (Scholarship@Western, 2019)
Contained on wax cylinders and lacquered aluminium discs, songs and stories are recorded by Robert and Elizabeth Thompson of Chief’s Point Indian Reserve #28. Not all recordings are considered sacred by the Anishinaabeg, instead the collection provides a broad range of topics including humour, the fur trade, plant medicine, and family history. Sometime before 1939, at the University of Western Ontario, Dr. Edwin Seaborn organized the production of 19 audio recordings. The March of Medicine in Western Ontario (1944) signaled to their creation by preserving the Saugeen Anishinaabeg oral tradition of the death of Tecumseh, a story that continues to live on within specific families at Saugeen First Nation #29. Through community-based research methods, evidenced through archival and artefact examinations, the story of the Anishinaabeg at Chief’s Point comes through this work. The voice of the land comes through the voices of the people cited within. A collaborative partnership with Museum London and Saugeen First Nation, the digitization of the audio collection was successfully completed. The songs and stories were repatriated to Saugeen and to other concerned communities through a series of community-driven presentations. The project was celebrated through the collaborative exhibition, The Voices of Chief’s Point (May to September 2018). The exhibit received the Lieutenant Governor’s Ontario Heritage Award for Excellence in Conservation (2019). This represents the first historic compilation of the Anishinaabeg at Chief’s Point as no publications exist on this specific group of people until now.